Notoginsenoside R1 for Organs Ischemia/Reperfusion Injury: A Preclinical Systematic Review - Tong, Qiang; Zhu, Peng-chong; Zhuang, Zhuang; Deng, Li-hui; Wang, Zi-hao; Zeng, Hua; Zheng, Guo-qing; Wang, Yan (Frontiers in Pharmacology, 2019)
Notoginsenoside R1 (NGR1) exerts pharmacological actions for a variety of diseases such as myocardial infarction, ischemic stroke, acute renal injury, and intestinal injury. Here, we conducted a preclinical systematic review of NGR1 for ischemia reperfusion (I/R) injury. Eight databases were searched from their inception to February 23rd, 2019; Review Manager 5.3 was applied for data analysis. CAMARADES 10-item checklist and cell 10-item checklist were used to evaluate the methodological quality. Twenty-five studies with 304 animals and 124 cells were selected. Scores of the risk of bias in animal studies ranged from 3 to 8, and the cell studies ranged from 3 to 5. NGR1 had significant effects on decreasing myocardial infarct size in myocardial I/R injury, decreasing cerebral infarction volume and neurologic deficit score in cerebral I/R injury, decreasing serum creatinine in renal I/R injury, and decreasing Park/Chiu score in intestinal I/R injury compared with controls (all P < 0.05 or P < 0.01). The multiple organ protection of NGR1 after I/R injury is mainly through the mechanisms of antioxidant, anti-apoptosis, and anti-inflammatory, promoting angiogenesis and improving energy metabolism. The findings showed the organ protection effect of NGR1 after I/R injury, and NGR1 can potentially become a novel drug candidate for ischemic diseases. Further translation studies are needed.